Posted by **Whitney** on Thursday, September 22, 2011 at 10:22pm.

By algebraic manipulation of the first two kinematic equations for one-dimensional motion:

1) vf = vi + at

2) xf = xi + (vi)(t) + (1/2)(a)(t)^2

Obtain the other two kinematic equations :

3) vf^2 - vi^2 = 2ax

4) xf = xi + (1/2)(vi + vf)t

- physics - 1 -
**Anonymous**, Friday, September 12, 2014 at 4:19pm
gh

## Answer this Question

## Related Questions

- Physics - 2.Using the kinematic equations, prove that if two balls are released ...
- Physical Science - Kinematic--v = v0 + at and Energy--½mv2 = mgh. Solve both ...
- science - Solve both equations for v. Kinematic: v=v0+at Energy: 1/2mv^2=mgh I ...
- help! - Can you please give me one of them so I cansolve for the other one?...
- physics - Starting from the constant-acceleration kinematic equations, write a ...
- Science( Physics[ Kinematic eqzns]) - Can the Kinematic equations be used if the...
- math - How do you solve system of equations and tell if they're consistant and ...
- Physics Changing Acceleration - Derive position, velocity, and acceleration ...
- Algebra - To solve the following system of equations by elimination, which step...
- math - can someone correct these for me. 8x –4y = 16 y = 2x –4 My answer: This ...